Geotechnical aspects of alluvial soils at different depths under sodium chloride action in Najran region, Saudi Arabia: Field supported by laboratory tests - El Aal, Ahmed Abd; Abdullah, Gamil M. S.; Zakaly, Hesham M. H.; Awad, Hamdy A.; Omar, Ali E.; Sakr, Mohamed A. H.; Ene, Antoaneta (Frontiers in Environmental Science, 2023)
Current research is aimed at studying the impact of sodium chloride (NaCl) on the performance of semi-arid soils in the Najran area of Saudi Arabia. Experimental work has been undertaken to invetigate how adding salt (NaCl) to the semi-arid soil collected in the Najran area affects the boundaries of Atterberg, compaction characteristics, California Bearing Ratio (CBR) and shear strength. All testing was done on soil samples from different zones of the Najran area at varying depths of 1.5, 3 and 4.5 meters along the soil profiles. The soil samples were analyzed individually and then compared with the same soil samples mixed with NaCl at different percentages of 5, 10, and 20% by weight of the dry soil, respectively. Using advanced techniques, such as the scanning electron microscope (SEM), energy dispersive x-ray analysis (EDX) and X-ray diffraction analysis (XRD), the stabilization process was examined. The findings revealed that NaCl has a significant impact on geotechnical characteristics of semi-arid soils. The maximum dry density (MDD) increased from 1.995, 1.93 and 1.96 to 2.02, 1.99 and 2.03 g/cm3 and the optimal water content (OMC) decreased from 9.47, 13.7 and 11.29 to 7.01, 9.58 and 8.09% with 20% NaCl added at various depths respectively. Shear resistance parameters were improved by adding 20% NaCl, where the soil cohesion increased from 0.1333, 0.0872 and 0.0533 to 0.1843, 0.1034 and 0.0372 kg/cm2 and the angel of internal friction increased from 24°, 25.5° and 29° to 27.8°, 30° and 33° respectively. The liquid and plastic limits and, in turn, plasticity index reduced as the added percentage of NaCl increased. Furthermore, significant increasing in the CBR percentages and reached to more than 50%. As a result, it is established that sodium chloride is an excellent stabilizer, especially at 20% concentration, and might be utilized as a sub-base substance in highway construction. Economic and technical benefits arise from the implementation of NaCl. The effects of salts addition on roads infrastructures are addressed.